Drug‐facilitated sexual assault (DFSA) involving 4‐methylethcathinone (4‐MEC), 3, 4‐Methylenedioxypyrovalerone (MDPV), and doxylamine highlighted by hair analysis. Issue 8 (24th April 2018) - Larabi, Islam Amine; Martin, Marie; Etting, Isabelle; Penot, Pauline; Fabresse, Nicolas; Alvarez, Jean Claude
Abstract: Recently, the emergence of new psychoactive substances (NPS) has led to their wide use among clubbers and men who have sex with men (MSM) for their stimulant effects. However, their use in drug‐facilitated sexual assault (DFSA) has rarely been described. Herein we report a case of a 44‐year‐old man who was assaulted after a party. Due to late reporting of the offense, only hair (black) was sampled 15 days later and a segmental analysis was achieved to look for most DFSA agents and NPS. Twenty mg of each segment (A: 0–1 cm, B: 1–3 cm, and C: 3–5 cm) were incubated in phosphate buffer pH 5.0. After alkaline liquid extraction and chromatographic separation on 1.9 μm Hypersil GOLD PFP column, compounds were detected by a TSQ Vantage mass spectrometer with electrospray ionization in positive mode with multiple reaction monitoring (MRM) acquisition. 4‐methylethcathinone (4‐MEC), methylenedioxypyrovalerone (MDPV) and doxylamine were found in proximal segment at very low concentrations (3, 5, and 9 pg/mg, respectively) which is in agreement with a single exposure in the previous month corresponding to the alleged facts. These substances were not detected in segments B and C showing a lack of repetitive exposure before the alleged event. Thus, the results do not contradict the patient's claim of being assaulted. Doxylamine has already been encountered in such cases but no publications referring to 4‐MEC or MDPV use have ever been documented. Our case reports the unusual administration of cathinones to achieve a sexual assault and stresses the interest of looking for designer drugs when dealing with DFSA cases. Abstract : The emergence of new psychoactive substances has led to their wide use in a recreational context for their stimulant effects. Herein we report an original case where two cathinones (4‐MEC and MDPV) were associated with doxylamine to achieve a sexual assault. This case was highlighted by hair analysis.